2013
DOI: 10.1016/j.semcancer.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication timing, genome stability and cancer

Abstract: Normal cellular division requires that the genome be faithfully replicated to ensure that unaltered genomic information is passed from one generation to the next. DNA replication initiates from thousands of origins scattered throughout the genome every cell cycle; however, not all origins initiate replication at the same time. A vast amount of work over the years indicates that different origins along each eukaryotic chromosome are activated in early, middle or late S phase. This temporal control of DNA replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 135 publications
(242 reference statements)
2
51
0
1
Order By: Relevance
“…(C,D) Higher magnification of retinas from WT (C) and Adamts18 −/− (D) littermates. GCL, ganglion cell layer; IPL, inner plexiform layer; INL, inner nuclear layer; OPL, outer plexiform layer (Donley and Thayer, 2013); ONL, outer nuclear layer. Scale bar: 200 μm.…”
Section: Resultsmentioning
confidence: 99%
“…(C,D) Higher magnification of retinas from WT (C) and Adamts18 −/− (D) littermates. GCL, ganglion cell layer; IPL, inner plexiform layer; INL, inner nuclear layer; OPL, outer plexiform layer (Donley and Thayer, 2013); ONL, outer nuclear layer. Scale bar: 200 μm.…”
Section: Resultsmentioning
confidence: 99%
“…point mutations, somatic copy number alterations and LOH arise because of erroneous repair of DNA lesions by various DNA repair pathways. Recently, it was reported that local DNA RT also affects the patterns of point mutations (4–6) and copy number alterations (4,7,8)—point mutations are enriched in late replicating regions, and end points of somatic copy number alterations, especially deletions, occur at a high frequency in late replicating regions (10). Here we reported that, in contrast, the LOH end points selectively occur in early replicating regions in multiple cancer types (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…DNA replication is spatially segregated such that some genomic regions are replicated early and others later during S phase (3). It was recently demonstrated that local DNA replication timing (RT) affects the patterns of point mutations (4–6), somatic copy number alterations (4,7,8) and rearrangements (9) in cancer and normal genomes—late replicating regions accumulate more mutations than early replicating regions (10). These findings prompt the question of whether LOH events, which are primarily replication-dependent phenomena, also show distinct patterns in the context of DNA RT.…”
Section: Introductionmentioning
confidence: 99%
“…If sustained for long periods it can lead to incompletely duplicated chromosomes that could undergo fragmentation or generate chromatin bridges, which in turn sustain chromosome rearrangements or tetraploidy (Burrell et al, 2013; Donley and Thayer, 2013; Russo et al, 2015). …”
Section: Gin At the Chromosomal Level: Routes To Aneuploidy And Pomentioning
confidence: 99%